2019
DOI: 10.3390/su11164364
|View full text |Cite
|
Sign up to set email alerts
|

Revising the Environmental Kuznets Curve for Deforestation: An Empirical Study for Bulgaria

Abstract: The evolution of human societies along with efforts to enhance economic welfare may well lead to the deterioration of the environment. Deforestation is a usual process throughout evolution that poses pressing and potentially irreversible environmental risks, despite the ecological and modernization processes that aim to limit those risks. The economic growth–environmental degradation relationship—namely, the environmental Kuznets curve (EKC) hypothesis—is studied in alignment with the autoregressive distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 56 publications
1
19
0
1
Order By: Relevance
“…Further, Waluyo and Terawaki (2016) found an inverted "U" shaped EKC for deforestation in Indonesia, with the income turning point estimated at $990. Using carbon dioxide emissions from deforestation as an index for environmental degradation, Tsiantikoudis et al (2019) found evidence of an inverted "N" shaped EKC in the short and long run, contrary to the standard EKC which is inverted "U" shaped. Ahmed and Long (2012) found evidence of an inverted "U" shaped EKC for deforestation for Pakistan.…”
Section: Introductionmentioning
confidence: 94%
“…Further, Waluyo and Terawaki (2016) found an inverted "U" shaped EKC for deforestation in Indonesia, with the income turning point estimated at $990. Using carbon dioxide emissions from deforestation as an index for environmental degradation, Tsiantikoudis et al (2019) found evidence of an inverted "N" shaped EKC in the short and long run, contrary to the standard EKC which is inverted "U" shaped. Ahmed and Long (2012) found evidence of an inverted "U" shaped EKC for deforestation for Pakistan.…”
Section: Introductionmentioning
confidence: 94%
“…However, resource use is distinguished into four categories: usage of material, water, land, energy, and climate change. Modern agriculture faces significant challenges, including extreme water supply and fertiliser impacts (Zamparas et al, 2019a), deforestation (Tsiantikoudis et al, 2019), GHG emissions (Kyriakopoulos & Chalikias, 2013, Kyriakopoulos et al, 2010, soil erosion, eutrophication (Zamparas et al, 2019b), and water pollution ( (Zamparas et al, 2020). Also, resource use efficiency means allocating and using various scarce resources to reach benefits.…”
Section: Classification Articles Based On Resource Efficiencymentioning
confidence: 99%
“…The Environmental Kuznets Curve (EKC) affirmed that industrial growth without GHG is increasing in most European countries. Tsiantikoudis S. et al [1] stated that the results of the ARDL approach cannot validate the inverted U-shape of the EKC hypothesis, but an inverted N-pattern was confirmed. This was attributed to a change in the energy consumption structure.…”
Section: Introductionmentioning
confidence: 98%